2013
DOI: 10.1093/jscr/rjt081
|View full text |Cite
|
Sign up to set email alerts
|

A double aortic arch presenting in the 7th decade of life

Abstract: A 64-year-old woman presented to the Vascular Outpatient department concerned about a pulsatile swelling in her right supraclavicular fossa. She had no other symptoms. A computed tomography angiogram demonstrated a double aortic arch (DAA) with the innominate artery arising from the right arch and left common carotid and subclavian arteries arising from the left arch. There were no aneurysms. A DAA accounts for 1% of congenital cardiac disease. It is the commonest form of a complete vascular ring, caused by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Presentation of DAA in an adult can occur from symptoms similar to those in childhood, especially from dysphagia due to compression of the esophagus. Reports of asymptomatic adults with DAA (such as our case) are sparse in the literature [4][5][6]. Certain factors increase the likelihood of diagnosing DAA in adulthood rather than childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presentation of DAA in an adult can occur from symptoms similar to those in childhood, especially from dysphagia due to compression of the esophagus. Reports of asymptomatic adults with DAA (such as our case) are sparse in the literature [4][5][6]. Certain factors increase the likelihood of diagnosing DAA in adulthood rather than childhood.…”
Section: Discussionmentioning
confidence: 99%
“…DAA is exceedingly rare, with one in 15,000 births accounting for only 1% of all congenital heart diseases [ 4 ]. The majority of DAA cases are diagnosed in infancy or childhood.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that its pathogenesis is related to genetic factors and its correlation with chromosomal abnormalities is as high as 24% [7]. McElhinney et al studied 66 cases of 22q11 chromosome microdeletions, 14% of which had clinical symptoms of DAA, which became an important etiological factor in the congenital double aortic arch [8, 9]. DAA often combines with other cardiovascular malformations, TOF is the most common [10].…”
Section: Discussionmentioning
confidence: 99%
“…(11,12) The literature reported very few cases diagnosed late or during adolescence or adulthood. (10,(13)(14)(15)(16)(17)(18) Clinically most of the anatomical variants are usually symptomatic especially that are associated with congenital heart defects, including also Fallot tetralogy. (12) Among symptomatic variants, without associated diseases, the most common is the constrictive traheo-esofagian vasculo-ligamentar ring.…”
Section: Discussionmentioning
confidence: 99%